EFFECT OF NITROGEN AND ZINC FERTILIZER ON PEARL MILLET (PENNISETUM GLAUCUM) UNDER AGRI-HORTI SYSTEM OF EASTERN UTTAR PRADESH - S. K. PRASAD; M. K. SINGH; SINGH, RENU; SINGH, RENU (The Bioscan, 2014)
A field experiment was conducted at RGSC farm of BHU, at Mirzapur (UP) during kharif season of 2010 with aim to find out suitable nitrogen and zinc fertilizer for pearl millet production under agri-horti system. The field experiment was laid out in a factorial randomized block design, with three replications, comprised with four nitrogen levels (0, 20, 40 and 60 kg N/ ha) and three levels of zinc (0, 5 and 10 kg Zn/ ha) with uniform rates of phosphorus and potassium at 40 and 30 kg/ha, respectively. Application of 60 kg N/ha and 10 kg Zn/ha recorded significant higher plant height, number of tillers, dry matter accumulation, number of panicle/plant, length of panicle, girth of panicle and yield. Grain/panicle and grain weight/panicle interact significantly with application of 40 kg N/ha × 10kgZn/ha. However, test weight interact significantly with 60 kg N/ha x 10kgZn/ha.